Disaster preparedness for dummies [videorecording (DVD)] - Mickelson, Robert; Waring, Todd; Reich, Stephen; Morzov, Shannon K. (--For dummies (Videorecording), 2005)
Information on how to be prepared for an emergency or natural disaster, such as hurricanes, tornadoes, flooding, wildfire, biological or chemical attack, explosions, or radiation threat.